1996
DOI: 10.1074/jbc.271.8.4251
|View full text |Cite
|
Sign up to set email alerts
|

An 11-Amino Acid Sequence from c-met Initiates Epithelial Chemotaxis via Phosphatidylinositol 3-Kinase and Phospholipase C

Abstract: Interaction of hepatocyte growth factor with its high affinity receptor c-met initiates a cascade of intracellular events leading to epithelial motility. An 11-amino acid sequence from the c-met receptor has been found to cause cell transformation in transfected fibroblasts (Ponzetto, C., Bardelli, A., Zhen, Z., Maina, F., Dalla, Z. P., Giordano, S., Graziani, A., Panayotou, G., and Comoglio, P. M. These findings demonstrate that the 11-amino acid sequence from c-met initiates epithelial motility via coinciden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
37
0

Year Published

1997
1997
2002
2002

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(38 citation statements)
references
References 21 publications
1
37
0
Order By: Relevance
“…Although it is generally believed that SH2 domains of p85 preferentially bind to receptor tyrosine kinases through this motif, other binding sites for p85 of PI3K have been described. For instance, p85 binding to the hepatocyte growth factor receptor family, including c-Met, c-Ron, and c-Sea is mediated by the YVHV sequence (31,32). Similarly, it has been demonstrated that amino acids YVNA on VEGFR-1 is a binding site for p85 (33).…”
Section: Vegfr-2 Activates Pi3kmentioning
confidence: 99%
“…Although it is generally believed that SH2 domains of p85 preferentially bind to receptor tyrosine kinases through this motif, other binding sites for p85 of PI3K have been described. For instance, p85 binding to the hepatocyte growth factor receptor family, including c-Met, c-Ron, and c-Sea is mediated by the YVHV sequence (31,32). Similarly, it has been demonstrated that amino acids YVNA on VEGFR-1 is a binding site for p85 (33).…”
Section: Vegfr-2 Activates Pi3kmentioning
confidence: 99%
“…3 H]inositol polyphosphates were analyzed by anion-exchange HPLC, using a Partisphere SAX column (Whatman), as described previously (2). All experiments were performed in triplicate.…”
Section: Ptdins-345-p 3 Directmentioning
confidence: 99%
“…Activation of the receptor-associated phosphoinositide 3-kinase (PI3K) 1 has been shown to cause mitogenesis and enhanced cell motility, although the exact mechanism by which PI3K mediates cell signaling during these events has been difficult to elucidate (1)(2)(3). The lipid products of PI3K have now been found to activate certain calcium-independent protein kinases C and to bind to a subset of Src homology 2 (SH2) domains (4,5).…”
mentioning
confidence: 99%
“…Precipitates were subjected to an in vitro kinase assay using g[ 32 P]ATP and phosphatidylinositol as substrates, according to Derman et al (1996). Brie¯y, beads were washed and incubated for 10 min at room temperature in kinase bu er containing 0.5 mM ATP, 20 mM MgCl 2 , 50 mM HEPES, pH 7.0, 0.25 mg/ml phosphatidylinositol and …”
Section: Pi3k Activitymentioning
confidence: 99%